Visions that change. Articulating the politics of participatory design. Issue 1 (2nd January 2020) - Huybrechts, Liesbeth; Teli, Maurizio; Zuljevic, Mela; Bettega, Mela
ABSTRACT: In this paper we draw upon the articles included in this special issue to question how to re-politicise co-design and participatory design (PD). Many authors in these fields have recently made a plea to re-engage with 'big issues' as a way to address this concern. At the same time, there is an increased attention into the micro-politics of the relations that are built-in co-design and PD. These two approaches are sometimes presented as working against each other with a de-politicising dynamic as a result. The editorial hypothesis of this issue is that designing visions can turn the tension between addressing the big issues and close attention to the particularity of relations into a motor for re-politicising design. Through engaging with literature, the articles presented in this issue, and two fieldwork cases that explore this dynamic, we discovered that paying careful attention to the activity of designing visions can support re-politicisation. While visions enable us to develop relations with close attention to their politics, building relations supports a more political approach to designing visions on issues. We argue that vision-making can particularly support re-politicisation when it enables the articulation of the political by relating its situated reality to how it unfolds in space and time.